Graphene/Ge Photoconductive Position-Sensitive Detectors Based on the Charge Injection Effect - Genglin Li; Jintao Fu; Feiying Sun; Changbin Nie; Jun Wu (Nanomaterials, 2023)
Position-sensitive detectors (PSDs) are of great significance to optical communication, automatic alignment, and dislocation detection domains, by precisely obtaining the position information of infrared light spots which are invisible to human eyes. Herein, a kind of PSD based on graphene/germanium (Ge) heterojunction architecture is proposed and demonstrated, which exhibits amplified signals by unitizing the charge injection effect. Driven by the graphene/Ge heterojunction, a large number of photogenerated carriers diffuse from the incident position of the light spot and subsequently inject into graphene, which ultimately generates a photoresponse with high efficiency. The experimental results show that the device can exhibit a fast response speed of 3 μs, a high responsivity of ~40 A/W, and a detection distance of 3000 μm at the 1550 nm band, which hints that the graphene/Ge heterojunction can be used as an efficient platform for near-infrared light spot position sensing.